(untitled) (Intent Research Scientific Journal, 2023)
The research paper discusses the problems of management in the digital economy, as well as the directions of development for their elimination. The necessity, possibility and expediency of introducing accurate (calculation) methods into the work of managers is noted. Within the framework of this task, the possibility of carrying out work on the creation and development of a parametric model of a social system operating in an active environment is shown to create appropriate techniques, tools, including computer programs for automating management activities, a simulation model of an enterprise, which can be used both in systems decision-making or decision support systems, and in training for the formation of decision-making skills.